2021
DOI: 10.3390/d13120618
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Pampus liuorum Liu & Li, 2013, Revealed by the DNA Barcoding of Pampus Fishes (Perciformes, Stromateidae)

Abstract: The genus Pampus contains seven valid species, which are commercially important fishery species in the Indo-Pacific area. Due to their highly similar external morphologies, Pampus liuorum has been proposed as a synonym of Pampus cinereus. In this study, partial sequences of COI (582 bp) and Cytb (1077 bp) were presented as potential DNA barcodes of six valid Pampus species and the controversial species P. liuorum. A species delimitation of the seven Pampus species was performed to verify their validities. Expl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
19
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 8 publications
(24 citation statements)
references
References 47 publications
(76 reference statements)
3
19
0
Order By: Relevance
“…With recent efforts, Pampus cinereus (Bloch, 1795), Pampus candidus (Cuvier, 1829), and Pampus punctatissimus (Temminck & Schlegel, 1845) are resurrected as valid species; Pampus liuorum Pampus minor Liu andLi, 1998, are published as new species (Liu and Li, 1998a;Liu and Li, 1998b;Liu et al, 2013a;Liu et al, 2013b;Liu and Li, 2013), demonstrating that the genus Pampus is actually a more diverse group. Our previous study, Wei et al (2021), confirmed the validities of seven species in the genus Pampus, viz., P. argenteus, P. candidus, P. chinensis, P. cinereus, P. liuorum, P. minor, and P. punctatissimus. However, validities of several species names, e.g., P. echinogaster and Pampus nozawae (Ishikawa, 1904), and Pampus griseus (Cuvier, 1833), remained unclear.…”
Section: Introductionsupporting
confidence: 75%
See 3 more Smart Citations
“…With recent efforts, Pampus cinereus (Bloch, 1795), Pampus candidus (Cuvier, 1829), and Pampus punctatissimus (Temminck & Schlegel, 1845) are resurrected as valid species; Pampus liuorum Pampus minor Liu andLi, 1998, are published as new species (Liu and Li, 1998a;Liu and Li, 1998b;Liu et al, 2013a;Liu et al, 2013b;Liu and Li, 2013), demonstrating that the genus Pampus is actually a more diverse group. Our previous study, Wei et al (2021), confirmed the validities of seven species in the genus Pampus, viz., P. argenteus, P. candidus, P. chinensis, P. cinereus, P. liuorum, P. minor, and P. punctatissimus. However, validities of several species names, e.g., P. echinogaster and Pampus nozawae (Ishikawa, 1904), and Pampus griseus (Cuvier, 1833), remained unclear.…”
Section: Introductionsupporting
confidence: 75%
“…There have been concerted efforts to study their reproductive biology, evolution, and population genetics of the Pampus species (e.g., Dadzie et al, 2000;Gupta, 2020;Fan et al, 2022). Nevertheless, the chaotic taxonomies and misidentifications have hindered our understanding of the biology and evolution of this genus (Liu et al, 2013a;Radhakrishnan et al, 2019;Wei et al, 2021).…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations
“…Divya et al [21] described the Pampus species collected from the Arabian Sea as a new species, P. candidus, but we think further scrutiny should be made to split more species from P. cinereus lineages before distinct morphological characters are identified. On the other hand, P. liuorum, a controversial Pampus species, was defined as a synonym of P. cinereus in our previous study [15], but a recent study justified P. liuorum as a valid species using two mitochondrial DNA barcodes [66]. In their Cytb trees, P. cinereus and P. liuroum sampled in the western Pacific were separated in two lineages, which was different from our result, but their COI tree corroborated our result that P. cinereus and P. liuroum are not reciprocal in monophyletic.…”
Section: Intraspecific Diversification Of P Chinensis and P Cinereusmentioning
confidence: 88%